If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 65 = 93 Reorder the terms: 65 + 4n = 93 Solving 65 + 4n = 93 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + 4n = 93 + -65 Combine like terms: 65 + -65 = 0 0 + 4n = 93 + -65 4n = 93 + -65 Combine like terms: 93 + -65 = 28 4n = 28 Divide each side by '4'. n = 7 Simplifying n = 7
| U=48n+210+7n+7 | | 18+2x=6y | | 1x+30=2x | | Y=2/9x-7 | | 1x+54=7x | | 2=10/3z=3z-7/3 | | 1/16a^2-1/25=0 | | a=8+b | | U=6*8n+6*35+7*n+7*1 | | =6*8n+6*35+7*n+7*1 | | x^2-208=0 | | f(a)=4x^2+2x+8 | | 2n+m-7m=-2 | | 5/6=-1/8x | | 1/3x2-4=21 | | 7x^2+6xy-y^2=0 | | 4(x+6)-3x=-2x+2-8 | | 0.7x-33.33=x+7 | | 11a-b+3a-(-7b)= | | w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 | | 3x-x=15 | | U=23n+240 | | 6x+9-7x-14=0 | | -3t(t-1)=2t+6 | | 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) | | s/616 |